The Effect of Using Clustering in Teaching Descriptive Text Writing to the Seventh graders at SMP 3 PSKD Jakarta - Agustina, Jessica Sarah (JET (Journal of English Teaching), 2017)
AbstractThe purpose of this study was to find out the effect of using clustering in teaching descriptive text writing skill to the seventh graders at SMP 3 PSKD Jakarta. It involved two groups: control and experimental. This implemented in different techniques; conventional method and clustering technique. The conventional method was implemented in the control class; while the clustering technique was implemented in the experimental class. Based on the findings, it was concluded that students need a technique to build students’ interested in writing. However, it should not be the only technique used to improve students’ writing skill. Keywords: Experimental research, clustering technique, descriptive text writing